2016
DOI: 10.1016/j.bbmt.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Infection Rates among Acute Leukemia Patients Receiving Alternative Donor Hematopoietic Cell Transplantation

Abstract: Alternative graft sources, [umbilical cord blood (UCB), matched unrelated donors (MUD), or mismatched unrelated donors (MMUD)] enable patients without a matched sibling donor to receive potentially curative hematopoietic cell transplantation (HCT). Retrospective studies demonstrate comparable outcomes among different graft sources. However, the risk and types of infections have not been compared among graft sources. Such information may influence the choice of a particular graft source. We compared the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 42 publications
3
65
0
Order By: Relevance
“…The majority of patients experienced at least one moderate to severe infection with bloodstream infection being the most common type of serious infection, similar to prior reports of infection burden after UCB transplantation 2931 . CMV and HHV-6 reactivation also occurred in the majority of patients as previously described in this patient population, although end organ involvement was rare 30, 32 . In the first 100 days after the thiotepa, TBI, and fludarabine regimen, median hospital length of stay was about 44 days, which is similar to that reported after double UCB transplant in a recent registry analysis comparing hospitalization among alternate graft sources 33 .…”
Section: Discussionsupporting
confidence: 72%
“…The majority of patients experienced at least one moderate to severe infection with bloodstream infection being the most common type of serious infection, similar to prior reports of infection burden after UCB transplantation 2931 . CMV and HHV-6 reactivation also occurred in the majority of patients as previously described in this patient population, although end organ involvement was rare 30, 32 . In the first 100 days after the thiotepa, TBI, and fludarabine regimen, median hospital length of stay was about 44 days, which is similar to that reported after double UCB transplant in a recent registry analysis comparing hospitalization among alternate graft sources 33 .…”
Section: Discussionsupporting
confidence: 72%
“…Ballen et al 23 compared the incidence of bacterial, viral and fungal infections in 1781 adults with acute leukemia who received alternative donor HCT between 2008 and 2011. Over 50% of patients developed bacterial infections by 1 year post HCT.…”
Section: Graft Sourcementioning
confidence: 99%
“…In multivariable analysis, bacterial infections were more common after mismatched unrelated donor (MMUD) than matched unrelated donor (MUD) grafts (P = 0.0295) and most common after umbilical cord blood (UCB) vs MUD (Po 0.001) or MMUD grafts (P = 0.0009), likely due to the slower engraftment and delayed immune recovery associated with UCB. 23 Although UCB are associated with increased BSI rates, Sanz et al 24 reported that higher CD8 + cell doses in UCB grafts independently associated with reduced risk of BSI.…”
Section: Graft Sourcementioning
confidence: 99%
“…Several groups have shown that T cell immune reconstitution after double or single CBT (with or without serotherapy) is delayed (14,15) and this, along with the naivety of the infused CB T cells, correlates with an increased risk of viral reactivation or infection from latent and lytic viruses like cytomegalovirus (CMV), Epstein Barr virus (EBV) and adenovirus in the post-transplantation period (16)(17)(18). A comparison of immune recovery after double CBT and HLA-matched unrelated donor (MUD) revealed delay in recovery of naive (CD45RO) memory (CD45RO+) CD4 + T cells, CD8 + T cells, and regulatory…”
Section: Introductionmentioning
confidence: 99%